MATERI DAN NILAI DI ERA GLOBALISASI: PERSPEKTIF APPADURAI - Agus Setyawan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2020)
The globalization era provides negative effects and positive effects. One of negative effect is that too much information can be misleading. But it also provides a positive effect that provides support space for parties who used to be on the periphery. Rural areas have become able to actively participate in global competition with the help of internet network technology. Before the globalization of commodities in the suburbs often unable to compete because the value is considered not quality. This is due to the lack of explanation and information about the socio-historical material of the commodity. As a result it is not widely known so that its value does not rise. Appadurai parses this with its globalization view which presents opportunities to increase material value by increasing access to information media networks that increasingly reach all regions. Appadurai divides this global era into five overlays, ideoscapes, technoscapes, financescapes, ethnoscapes, mediascapes. This study uses a literary research model with primary data from Appadurai's books and other similar articles, especially those that discuss Appadurai's thinking about globalization. From this the rural (rural) region with all its material bases has the potential to compete with other regions. The result is that each material will increase its selling value as long as the material has a meaningful difference to the others. .